Composite from high density polyethylene (HDPE) reinforced with rice husks (Oryza sativa): Preparation and mechanical property / Norin Zamiah Kassim Shaari, Ahmad Redha Taha and Suhaiza Hanim Hanipah - Kassim Shaari, Norin Zamiah; Taha, Ahmad Redha; Hanipah, Suhaiza Hanim (Universiti Teknologi MARA Shah Alam, 2020)
In this study, the composite from HDPE polymer was formulated with the incorporation of Oryza sativa also known in general as rice husks or hulls with two different methods: with the incorporation of plasticiser (glycerol and citric acid) and without plasticisers. The ratio of glycerol to citric acid used in the experiment was 1:2. The aim of this study is to determine the effect of incorporating rice husk with different fibre sizes on the mechanical properties of the HDPE composite. The blending of HDPE with the rice husk was performed in a mixer in processing compounding polymer followed by the extrusion process. Results show that in the absence of the plasticiser, rice husk portrays good compatibility with HDPE polymer, where the composite possessed good tensile strength and elongation. The best plasticising effect was portrayed by filler with 100 µm as it yields the highest tensile strength and strain. In conclusion, the composite could be potentially used for suitable applications, which requires flexible material with better processing ability and would not be brittle.